Hemochorial placentation: development, function, and adaptations†. Issue 1 (22nd February 2018) - Soares, Michael J; Varberg, Kaela M; Iqbal, Khursheed
Abstract: Placentation is a reproductive adaptation that permits fetal growth and development within the protected confines of the female reproductive tract. Through this important role, the placenta also determines postnatal health and susceptibility to disease. The hemochorial placenta is a prominent feature in primate and rodent development. This manuscript provides an overview of the basics of hemochorial placental development and function, provides perspectives on major discoveries that have shaped placental research, and thoughts on strategies for future investigation. Abstract : The review presents basic concepts of hemochorial placentation, discusses significant contributions to the field, and highlights experimental approaches for future investigation.